Membangun Kesehatan Mental Perempuan Dalam Pesprektif Al-Hujurat Ayat 11 - -, Yeti Dahliana; Rohma Syarifah Az Zaroh (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
This research was written from the results of analyzing emotional anxiety disorder (excessive anxiety) which greatly affects women's mental health, caused by other people who cannot keep their words well. Women are creatures created to accompany men as pairs, not closing the possibility will be faced with various complex problems and affect mental health. Responding to this can be pursued by building women's mental health from the view of the Qur'an and reviewed from a psychological perspective. This research uses a qualitative method, focusing on library research (library research) which is used to collect various information and data with the help of various sources, such as magazines, journals, books, the Qur'an, previous journal publications, and so on. The results of this study can show that building women's mental health in the perspective of Surah al-Hujurat verse 11 can be asked by learning to be silent, self-meditation, not easily assuming and being able to accept advice, giving alms for women who can increase happiness in themselves, thus creating mental health in women.